Muscle-Organ Crosstalk: Focus on Immunometabolism - Bay, Marie Lund; Pedersen, Bente Klarlund (Frontiers in Physiology, 2020)
Skeletal muscle secretes several hundred myokines that facilitate communication from muscle to other organs, such as, adipose tissue, pancreas, liver, gut and brain. The biological roles of myokines include effects on e.g. memory and learning, as well as glucose and lipid metabolism. The present minireview focuses on recent developments showing that exercise-induced myokines are involved in immunometabolism of importance for the control of e.g. tumor growth and chronic inflammation. In this review, immunometabolism is discussed as the non-immune related pathologies, leading to an immune response and some degree of inflammation, which promotes metabolic abnormalities.